BUDAYA KORUPSI DALAM PENGADAAN BARANG DAN JASA DI INDONESIA - Annissa Herminda; Yesica Laurensa; Elsi Kartika Sari (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
The central issue of this study is the persistence of corruption culture in Indonesia’s public procurement, despite regulatory reforms such as Presidential Regulation No. 16 of 2018 and its amendments. The research aims to analyze systemic factors sustaining corruption, identify regulatory weaknesses, and propose reform strategies to establish clean and integrity-based procurement governance. A qualitative approach was employed, combining normative-empirical analysis through regulatory review, corruption case data from the Corruption Eradication Commission (KPK), and literature studies on public procurement practices. The findings reveal that corruption in procurement is multidimensional, driven by weak law enforcement institutions, political pressures, and limited coordination among oversight bodies, resulting in state losses, declining public service quality, and weakened public trust. Nevertheless, positive developments include increasing legal awareness, public participation through whistleblowing, and the digitalization of procurement systems. This study concludes that structural reforms and legal culture transformation are essential prerequisites for positioning procurement as an effective instrument of social engineering and distributive justice.Keywords: Corruption culture, Public procurement, Transparency, Structural reform, Legal culture